The Effect of Customer Satisfaction on Behavioral Intentions: A Study on Consumer Behavior of Car Insurance Consumers in Melbourne, Australia - Wahyuningsih, Wahyuningsih; Nurdin, Djayani (International Research Journal of Business Studies, 2010)
It has often been argued that customer satisfaction can contribute significantly to a company’s success in a variety of ways. This research aims to investigate the effect of customer satisfaction on behavioural intentions. Two determinants of behavioral intentions examined in this study namely repurchase intentions and positive word-of-mouth communication. The model has been tested using surveyed data from 546 car insurance consumers in Melbourne, Australia. The empirical results of this study show that the higher the level of satisfaction, the higher the consumer’s intentions to repurchase and inform positive information about the purchased product and company to other people. This means that the more satisfied the consumers the more likely they are to repurchase car insurance from the same company and more likely to do positive word-of-mouth communication. Thus, behavioral intentions expressed by consumers depend on their levels of satisfaction. Hence, the company might maintain their existing customers and attract new consumers to achieve better financial performance. Discussion and managerial implications are provided based on research results.